The Role of Civil Law in Legality Transactions E-Commerce - Berliana Adinda Ayu Puspita (The International Conference on Education, Social Sciences and Technology (ICESST), 2022)
Sales and purchase agreements that occur electronically between sellers and buyers create online buying and selling. Internet and social media users in Indonesia, online E-Commerce businesses are increasingly growing. E-Commerce is business activities involving consumers, manufacturers, service providers and intermediaries using computer networks, namely the internet. E-Commerce users are also of various ages, because there are many conveniences when shopping online, just open the desired E-Commerce application, choose the items you buy and the goods arrive as desired within a few days. The increasing number of online buying and selling has indirectly influenced changes in legal regulations. The rules that apply in Indonesia are still unclear regarding electronic buying and selling. This is due to the fact that the conditions necessary for the validity of an electronic agreement have not been specifically regulated. The aim of this research is to determine the validity of electronic contract agreements in E-Commerce transactions in terms of civil law. In this research, normative research methods were used. This method involves processing data from legal regulations and applying rules or norms as the basis for research. Research results Electronic documents are binding and recognized as valid evidence to provide legal certainty regarding the operation of electronic systems and electronic transactions, especially for proof and related to legal actions carried out through electronic systems